PKMYT1 knockdown inhibits cholesterol biosynthesis and promotes the drug sensitivity of triple-negative breast cancer cells to atorvastatin - Gao, Wei; Guo, Xin; Sun, Linlin; Gai, Jinwei; Cao, Yinan; Zhang, Shuqun (PeerJ, 2024)
Triple negative breast cancer (TNBC) as the most aggressive molecular subtype of breast cancer is characterized by high cancer cell proliferation and poor patient prognosis. Abnormal lipid metabolism contributes to the malignant process of cancers. Study observed significantly enhanced cholesterol biosynthesis in TNBC. However, the mechanisms underlying the abnormal increase of cholesterol biosynthesis in TNBC are still unclear. Hence, we identified a member of the serine/threonine protein kinase family PKMYT1 as a key driver of cholesterol synthesis in TNBC cells. Aberrantly high-expressed PKMYT1 in TNBC was indicative of unfavorable prognostic outcomes. In addition, PKMYT1 promoted sterol regulatory element-binding protein 2 (SREBP2)-mediated expression of enzymes related to cholesterol biosynthesis through activating the TNF/ TNF receptor-associated factor 1 (TRAF1)/AKT pathway. Notably, downregulation of PKMYT1 significantly inhibited the feedback upregulation of statin-mediated cholesterol biosynthesis, whereas knockdown of PKMYT1 promoted the drug sensitivity of atorvastatin in TNBC cells. Overall, our study revealed a novel function of PKMYT1 in TNBC cholesterol biosynthesis, providing a new target for targeting tumor metabolic reprogramming in the cancer.
Keywords: Triple-negative breast cancer; PKMYT1; TNF/TRAF1/AKT pathway; Lipid metabolism; Atorvastatin